1989
DOI: 10.1080/02640418908729834
|View full text |Cite
|
Sign up to set email alerts
|

Ritual and free‐throw shooting in basketball

Abstract: The purpose of this study was to determine the nature and effect of certain highly patterned behaviours utilized prior to free-throw shooting in basketball. Ten female basketball players comprising the varsity squad of Texas Christian University, Fort Worth, Texas, USA served as subjects for this study. Subjects were filmed with a high-speed camera and monitored for heart rate during the performance of 10 free throws in each of two conditions: ritual and non-ritual. For the ritual condition, subjects were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Whether for the highly skilled, moderately proficient, or beginner, preperformance routines can enhance achievement (Lidor & Singer, 2000). For example, for a novel ball tossing task (Singer et al, 1993) or a basketball free throw (Southard, Miracle, & Landwer, 1989;Wrisberg & Anshel, 1989;Wrisberg & Pain, 1992), participants who were taught how to use a particular routine attained a higher level of skill than those who were not trained to use one. Perhaps one reason is that the activation of a consistent routine associated with an act of skill provides the performer with perceptions of control, of being able to make something good happen.…”
Section: Expertise In Self-paced Events / 369mentioning
confidence: 99%
“…Whether for the highly skilled, moderately proficient, or beginner, preperformance routines can enhance achievement (Lidor & Singer, 2000). For example, for a novel ball tossing task (Singer et al, 1993) or a basketball free throw (Southard, Miracle, & Landwer, 1989;Wrisberg & Anshel, 1989;Wrisberg & Pain, 1992), participants who were taught how to use a particular routine attained a higher level of skill than those who were not trained to use one. Perhaps one reason is that the activation of a consistent routine associated with an act of skill provides the performer with perceptions of control, of being able to make something good happen.…”
Section: Expertise In Self-paced Events / 369mentioning
confidence: 99%
“…It seems that SMDS of the flexor carpi radialis muscle had a negative impact on FTP. The percentage of the following two FTs (columns 12 and 13) has increased; considering the widely documented nonexistence of long-lasting effects of stretching exercises on the resistance of the muscle-tendon unit [31,32,33], we assumed that negative effects of the SMDS of the flexor carpi radialis muscle have a relatively short duration (~5'-10').…”
Section: Discussionmentioning
confidence: 99%
“…Some previous experimental studies have examined performance outcomes using two conditions, with and without the use of a PPR [13,26,32]. The general conclusion was that performance is significantly better when using a PPR, but researchers have not examined the effect of substituting one behavioral routine for another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Southard, Miracle, and Landwer (1989) asked 10 varsity female basketball players to perform 10 free throws under two conditions: ritual and nonritual. Results revealed that players made more baskets in the regular condition 452 Interventions and Performance Enhancement than when omitting a commonly used routine.…”
Section: Manipulations Of Regular Routines Performed By the Participamentioning
confidence: 99%